Analisis Pengendalian Kualitas Produksi Tabung Gas LPG 3KG dengan Pendekatan Six sigma pada PT ABC - Nudin, Muhamad Ihsan; Sukanta, Sukanta; Alfanadim, Andraya (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Quality control is essential to ensure that products meet predetermined specifications and align with company policies. Based on PT XYZ’s production report from December 2023, the number of defective products requiring repairs was notably high, reaching 17.3% of the total 98,852 gas cylinders produced within 19 days. This study aims to evaluate the quality control performance and identify the factors influencing it. The Six sigma DMAIC method was applied to assess performance. At the measurement stage, the Defects Per Million Opportunities (DPMO) was found to be 44,743, corresponding to a sigma value 3.203. The study identified four key factors contributing to production defects: machinery, materials, personnel, and methods. Although the company's quality control efficiency is deemed satisfactory, it has yet to prevent a significant sales decline of 20-40%. Therefore, implementing Six sigma analysis is expected to uncover processes that can reduce manufacturing defects in 3 kg LPG cylinder production. By addressing these issues, the company can improve product quality, maintain customer satisfaction, and enhance competitiveness in the market. Keywords: DMAIC, DPMO, Quality Control, Six sigma